PREVALENCE OF VITAMIN D DEFICIENCY IN DIFFERENT GROUPS OF CHRONIC RENAL FAILURE PATIENTS. - Bistra T. Galunska; Daniela I. Gerova; Dobrin N. Paskalev; Rositza Y. Zorcheva; Valentin Ch. Ikonomov; Valentin Vladimirov; Dobrin A. Svinarov (Peytchinski Publishing, 2015)
Purpose: To determine and compare the vitamin D status of different groups CKD patients on hemodialysis, peritoneal dialysis, or no renal replacement therapy and to evaluate the effect of vitamin D therapy. Patients and Methods: This pilot study enrolled 40 consecutive CKD patients (21 men, 19 women) divided into three groups: 15 CKD patients in 1,2,3,4 stage of the disease without renal replacement therapy (RRT); 10CKD patients on hemodialysis (HD) and 15 CKD patients on peritoneal dialysis (PD), ten of which were on vitamin D therapy. Vitamin D status was determined by serum 25-xydroxyvitamin D (25OHD). Results: Ninety percent of patients were in vitamin D deficiency/insufficiency; and only 4 patients (10.0%) reached 25OHD levels above 75nmol/L. The median 25OHD level was 31.15nmol/L (interquartile range: 16.67-48.33nmol/L).Tendency of worse vitamin D status in women than in men was observed. Higher 25OHD levels were found in pre-dialysis patients (median 44.81nmol/L, 25%-75% percentile 16.24-52.21nmol/L) and lower in HD (median 31.15nmol/L, 25%-75% percentile 13.04-64.45nmol/L) and PD patients (median 33.38nmol/L, 25%-75% percentile 23.15-48.49nmol/L), but the difference did not reach statistical significance. Better vitamin D status was found in the PD group of patients receiving vitamin D preparations (p<0.05). Conclusions: 25OHD deficiency/insufficiency is prevalent in renal failure patients with or without renal replacement therapy. It seems that vitamin D therapy improves the vitamin D status of PD patients. Further larger studies are needed to clarify the effect of specific type vitamin D therapy on serum 25OHD levels and clinical outcome in different groups of CKD patients.